Tolerance analysis of a GFET transistor for aerospace and aeronautical application. Issue 1 (January 2021) - Lamberti, P; Mura, M La; Pasadas, F; Jiménez, D; Tucci, V
Abstract: Due to the high carrier mobility, graphene is considered a promising material for use in high-speed electronic devices in the post-silicon electronic era. Graphene high resistance to radiation and extreme temperatures makes the development of graphene-based electronics a key-enabling technology for aerospace, defence, and aeronautical applications. Nevertheless, achieving uniform device-to-device performance is still a challenge, and these fields require high reliability components. In particular, many critical issues remain to be solved, such as their reproducibility and guaranty of identical performances against possible variations of different manufacturing and environmental factors. In the present work, a model capable to take into account the physical characteristics linked to the production process of a Graphene Field-Effect Transistor (GFET) is exploited to carry out a tolerance analysis of process-related geometrical parameters on the device performance. The most influential parameters that affect the device behaviour are studied in order to enhance the fabrication yield.